Barahviraat - Sharma, Seema; Sharma, M. L. (Delhi : Jahanvi, 2018)
It is double love triangle of love and sacrifice includes interesting, laughable incidents. It is a translation of Shakespeare's play Twelfth Night. Duke Love a Rich lady who loves Duke's assistant- actually a lady working as man. All this makes interesting incidents.